Multiple congenital defects associated with trisomy for long arm of No. 4. Issue 4 (August 1976) - Issa, M; Potter, A M; Blank, C E
Abstract : The clinical and cytogenetic findings of a male infant with multiple congenital anomalies and trisomy for the distal third of the long arm of No. 4 are described. The abnormal chromosome was inherited from the mother who had a balanced translocation, t(4;9)(q31;q34). Trisomy for the long arm of No. 4 has previously been described in only 3 patients.